Efektivitas Prenatal Yoga Terhadap Tingkat Kecemasan Ibu Hamil Trimester III Dalam Menghadapi Persalinan Di Kelas Ibu Hamil Posyandu Dahlia - Flora Natalia Simanjuntak; Resi Galaupa (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2023)
Anxiety in pregnant women will have an impact on the physical and psychological conditions of the mother and fetus. Anxiety in pregnancy can arise because of the long waiting period in waiting for the delivery process, especially in primigravidarum pregnant women. One of the physical exercises that is recommended and proven to be effective in reducing anxiety during pregnancy is yoga. This study aims to determine the Effectiveness of Prenatal Yoga on the Anxiety Level of Third Trimester Pregnant Women in Facing Labor in the Class of Pregnant Women at Posyandu Dahlia. The design used is Pret-test-post-test design. Total population of 41 pregnant women, a sample of 30 people, sampling using purposive sampling. From the Wilcoxon test statistic with a significant level of Î± = 0.05, a significant assumption is obtained of 0.038 <0.05, thus Ha is accepted, which means that there is a positive effect between dhikr therapy and a decrease in anxiety levels in pregnant women at Posyandu Dahlia. This shows that there is a decrease in the level of anxiety in the subject after being given treatment in the form of prenatal yoga. So it is suggested for future researchers to examine more factors that cause severe or very severe levels of anxiety in prigravida pregnant women.